2019
DOI: 10.3389/fpsyg.2019.02641
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Factor Structure and Measurement Invariance by Gender for a Modified Shortened Adapted Social Capital Assessment Tool in India

Abstract: Social capital is defined as the nature of the social relationship between individuals or groups and the embedded resources available through their social network. It is considered as a critical determinant of health and well-being. Thus, it is essential to assess the performance of any tool when meaningfully comparing social capital between specific groups. Using measurement invariance (MI) analysis, this paper explored the factor structure of the social capital of men and women measured by a modified Shorten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 76 publications
3
9
0
Order By: Relevance
“…Before performing FA, we assessed the possible number of latent constructs that could emerge from the data using Horn's parallel analysis [36], which indicated that only one latent measure could be extracted from the data, consistent with our conceptualization. We implemented the factor analytical model with one latent measure, which presented adequate goodness of fit to the data [37]. We observed robust factor loadings and relatively smaller residuals, indicating a high construct validity of the observed latent measure [38] (See Additional File 1).…”
Section: Estimation Of the Summary Measure Of Outputs And Its Descriptive Explorationmentioning
confidence: 98%
“…Before performing FA, we assessed the possible number of latent constructs that could emerge from the data using Horn's parallel analysis [36], which indicated that only one latent measure could be extracted from the data, consistent with our conceptualization. We implemented the factor analytical model with one latent measure, which presented adequate goodness of fit to the data [37]. We observed robust factor loadings and relatively smaller residuals, indicating a high construct validity of the observed latent measure [38] (See Additional File 1).…”
Section: Estimation Of the Summary Measure Of Outputs And Its Descriptive Explorationmentioning
confidence: 98%
“…The measure of social capital of the household heads and the communities were the primary explanatory variables of this study. During the survey, each household head responded to the Shortened and Adapted Social Capital Assessment Tool in India (SASCAT-I) ( Hasan et al, 2019 ), where they reported their community participation (2 questions), collective action (2 questions), social support (3 questions), social cohesion (3 questions), and trust (3 questions). These responses were categorized into 12 categorical indicators and used as the input for a multilevel confirmatory factor analytical model (MCFA), considering each household head as level one (n = 6218) and community as level two (n = 346) ( Heck & Thomas, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…We consulted relevant literature to measure the three types of capital ( Wu, 1999 ; Li and Yu, 2005 ; Zhang, 2006 , 2015 ; Su and Hwang, 2009 ; Hasan et al, 2019 ). Social capital was measured by asking student athletes to rate, on a five-point Likert-type scale from strongly disagree (1) to strongly agree (5), how true the following three statements were: “My family cares about my studies,” “My family discusses school affairs with me,” and “My family discusses my plans for the future with me.” Cultural capital was measured using ratings for the following four statements: “I go to bookstores,” “I listen to classical music,” “I attend concerts or plays,” “I visit museums, in particular, art museums,” and “I visit various exhibitions, such as art exhibitions and book exhibitions.” Financial capital was measured using the statements “I own athletic clothing,” “I own sporting equipment,” and “I own sporting accessories.” We also asked about cultural influences that impede socioeconomic advancement (negative cultural factors) by using the statements “I play video games regularly,” “I smoke regularly,” and “I have a rich nightlife” (Cronbach’s α = 0.71).…”
Section: Mateials and Methodsmentioning
confidence: 99%
“…Regarding their educational aspiration, Coleman (1988) noted that such aspiration is affected by an individual’s social, cultural, and financial capital. Previous studies have demonstrated that consistent social capital – from parents, teachers, and peers – drives student athletes to persist in their training ( Fawcett et al, 2009 ; Hung, 2012 ; Zheng and Hung, 2018 ; Hasan et al, 2019 ). Social capital manifests as parents investing resources – including time, money, and energy – to support their children’s educational goals ( Xie, 2014 ).…”
Section: Introductionmentioning
confidence: 99%